Comparison of Helicopter Emergency Medical Services Transport Types and Delays on Patient Outcomes at Two Level I Trauma Centers. (4th May 2017) - Nolan, Brodie; Tien, Homer; Sawadsky, Bruce; Rizoli, Sandro; McFarlan, Amanda; Phillips, Andrea; Ackery, Alun
Abstract: Background : Helicopter emergency medical services (HEMS) have become an engrained component of trauma systems. In Ontario, transportation for trauma patients is through one of three ways: scene call, modified scene call, or interfacility transfer. We hypothesize that differences exist between these types of transports in both patient demographics and patient outcomes. This study compares the characteristics of patients transported by each of these methods to two level 1 trauma centers and assesses for any impact on morbidity or mortality. As a secondary outcome reasons for delay were identified.Methods : A local trauma registry was used to identify and abstract data for all patients transported to two trauma centers by HEMS over a 36-month period. Further chart abstraction using the HEMS patient care reports was done to identify causes of delay during HEMS transport.Results : During the study period HEMS transferred a total of 911 patients of which 139 were scene calls, 333 were modified scene calls and 439 were interfacility transfers. Scene calls had more patients with an ISS of less than 15 and had more patients discharged home from the ED. Modified scene calls had more patients with an ISS greater than 25. The most common delays that were considered modifiable included the sending physician doing a procedure, waiting to meet a land EMS crew, delays for diagnostic imaging and confirming disposition or destination.Conclusions : Differences exist between the types of transports done by HEMS for trauma patients. Many identified reasons for delay to HEMS transport are modifiable and have practical solutions. Future research should focus on solutions to identified delays to HEMS transport.Key words : helicopter emergency medical services; trauma; prehospital care; delays